1999
DOI: 10.1046/j.1365-2222.1999.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation and altered alveolar macrophage phenotype pattern after repeated low‐dose allergen exposure of atopic asthmatic subjects

Abstract: Repeated low-dose allergen exposure induces an allergic airway inflammation in asthmatic subjects. The inflammation is associated with an altered AM phenotype pattern, consistent with an influx of monocytes and a hypothetical increased accessory cell function in the airways, possibly contributing to the development and sustenance of airway inflammation in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
49
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 40 publications
6
49
0
Order By: Relevance
“…CD11b is a component of a-chains of b 2 integrins (52). Higher expression of CD11b reflects the activation of pulmonary macrophages (48,53). Indeed, adoptive transfer of CD11b + pulmonary macrophages induces exaggerated AHR and airway inflammation in a mouse model of asthma (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD11b is a component of a-chains of b 2 integrins (52). Higher expression of CD11b reflects the activation of pulmonary macrophages (48,53). Indeed, adoptive transfer of CD11b + pulmonary macrophages induces exaggerated AHR and airway inflammation in a mouse model of asthma (54).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adoptive transfer of CD11b + pulmonary macrophages induces exaggerated AHR and airway inflammation in a mouse model of asthma (54). This suggests that these cells may contribute to the pathogenesis of AHR and inflammation, particularly in relation to recurrent infections (53,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have demonstrated that late asthmatic reaction may occur at doses lower than those inducing early reaction [7]. Indeed, repeated inhalation of low doses, without clinical symptoms, increases bronchial hyperresponsiveness and eosinophil cationic protein levels [19,20]. This continuous exposure without symptoms may also increase the production of antibodies [9].…”
Section: Discussionmentioning
confidence: 99%
“…The current authors have demonstrated that the fall in FEV1 during the specific challenge can be compared to the distribution of the values of FEV1 during the control test with lactose [3]. If the inhaled dose is measured, the specific reactivity can be expressed as the provocative dose of flour causing a 20% or 15% fall in FEV1 (PD f 20 or PD f 15, respectively). Several studies of various allergens have shown that the range of specific reactivity among asthmatic subjects is wide [3,[6][7][8][9].…”
mentioning
confidence: 95%
“…In a diluent controlled evaluation of the challenge, the percentage of eosinophils, interleukin-5 and eosinophil cationic protein in induced sputum were shown to increase [2], and early effects on eosinophils and macrophages in bronchoalveolar lavage fluid have also been reported [9,10]. The aim of the current study was to further characterise the influence of repeated low-dose allergen challenge on the development of airway inflammation.…”
mentioning
confidence: 87%